Once upon an eid ebook Stories of hope and joy by 15 muslim voices. - Ali, S. K. (2020)
A joyous short story collection by and about Muslims, edited by New York Times bestselling author Aisha Saeed and Morris finalist S. K. Ali Once Upon an Eid is a collection of short stories that showcases the most brilliant Muslim voices writing today, all about the most joyful holiday of the year: Eid! Eid : The short, single-syllable word conjures up a variety of feelings and memories for Muslims. Maybe it's waking up to the sound of frying samosas or the comfort of bean pie, maybe it's the pleasure of putting on a new outfit for Eid prayers, or maybe it's the gift giving and holiday parties to come that day. Whatever it may be, for those who cherish this day of celebration, the emotional responses may be summed up in another short and sweet word: joy . The anthology will also include a poem, graphic-novel chapter, and spot illustrations. The full list of Once Upon an Eid contributors include: G. Willow Wilson ( Alif the Unseen, Ms. Marvel ), Hena Khan ( Amina's Voice, Under My Hijab ), N. H. Senzai ( Shooting Kabul, Escape from Aleppo ), Hanna Alkaf ( The Weight of Our Sky ), Rukhsana Khan ( Big Red Lollipop ), Randa Abdel-Fattah ( Does My Head Look Big in This? ), Ashley Franklin ( Not Quite Snow White ), Jamilah Thompkins-Bigelow ( Mommy's Khimar ), Candice Montgomery ( Home and Away, By Any Means Necessary ), Huda Al-Marashi ( First Comes Marriage ), Ayesha Mattu, Asmaa Hussein, and Sara Alfageeh.